The Personal Investment Guide For Executives and Professionals - Schulman, Martin (Bud). (Washington Acropolis Books, 1971)
The Personal Investment Guide For Executives and Professionals. This book should be read by all professionals who need common sense advice and, more important, a warning against the fascinating prospects of making a sure and quick dollar with little investment, tremendous leverage, full tax benefits and the wish to be known as a shrewd, if only parttime, capitalist.
Keywords: Economics